JURNAL ILMU KEHUTANAN : An Innovative Policy For Rural Development? Rethinking Barriers To Rural Communities Earning Their Living From Forests In Indonesia - Ahmad Maryudi (Fakultas Kehutanan UGM, 2014)
The government of Indonesia (GoI) has trialed a number of community forestry schemes, ranging from collaborative management to long term forest management rights handed to local communities, and implements them in state forestland.